2015
DOI: 10.1097/md.0000000000002013
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prediction Model Using Clinico-Pathologic Characteristics for Nonsmall Cell Lung Cancer Patients After Curative Resection

Abstract: The current TNM staging system did not provide disease relapse information. The aim of study was try to establish a predictive survival model for disease and overall survival in nonsmall cell lung cancer patients who presented as resectable disease and to develop a reference for follow-up imaging tool selection.From January 2005 to December 2011, 442 patients who initially presented as resectable disease (stages I–IIIa) and received anatomic resection and mediastinal lymph node dissection were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
9
1
1
Order By: Relevance
“…Among these clinical scenarios, primary pulmonary malignancy is a major concern, and tissue proof or resection is recommended if images change in the serial follow-up. In patients who underwent tumor resection and were confirmed with primary pulmonary malignancy, the risk of disease relapse was the major concern whereby the reported early relapse in patients with resectable non-small cell lung cancer is 10-19% [5,29]. Many prognostic factors have been identified but can only be used for surveillance planning [3][4][5], instead of relapse prediction [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these clinical scenarios, primary pulmonary malignancy is a major concern, and tissue proof or resection is recommended if images change in the serial follow-up. In patients who underwent tumor resection and were confirmed with primary pulmonary malignancy, the risk of disease relapse was the major concern whereby the reported early relapse in patients with resectable non-small cell lung cancer is 10-19% [5,29]. Many prognostic factors have been identified but can only be used for surveillance planning [3][4][5], instead of relapse prediction [30].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with lung cancer who present with resectable disease, Diagnostics 2020, 10, 144 2 of 15 the major factor that affects patients' survival is recurrence. A literature review revealed that many relapse risk factors have been identified from clinicopathologic characteristics, and prediction models have been proposed [3][4][5][6]. These findings have been used to identify high-risk patients and for the planning of personalized surveillance programs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated such result. Wu CY et al 16 has established a predictive survival model for survival in patients with NSCLC who received radical resection and identified tumor size, visceral pleural invasion, and patients with lymph node metastasis as independent prognostic factor for DFS. Huang H et al 17 reported that visceral pleural invasion is a size-independent poor prognostic factor in stage I NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of specific early symptoms, the patients with lung cancer are neglected in initial stage and are frequently diagnosed in an advanced stage. Management of lung cancer usually entails radiotherapy, chemotherapy, targeted therapy, and immunotherapy following surgery [3]; however, the five-year survival rate is only approximately 25-30% [4,5]. And, thus, it is imperative to develop novel antitumour drugs or methods for alleviating or postponing the progress of lung cancer.…”
Section: Introductionmentioning
confidence: 99%